Chlorosulfonation of Acetanilide to Obtain an Intermediate for the Preparation of a Sulfa Drug - Keerthi, D. Shruthi (Asian Journal of Pharmaceutics (AJP), 2017)
Aim: The major scope of the work is to find best suitable conditions and process for the preparation of sulfa drug where the yield can be maximum with reduced periods. Materials and Methods: Sulfathiazole is prepared by chlorosulfonation of acetanilide (at 114Â°C) to obtain an intermediate which is reacted with 2-aminothiazole. The samples of intermediate and 2-aminothiazole with ratios (3:1, 1:1, and 1:3) and with different acid acceptors named pyridine, sodium bicarbonate, dimethylaniline, and ammonium hydroxide are studied. Results and Discussion: Chlorosulfonation at 114Â°C yielded good which further gave good results (91% yield) with 3:1 intermediate and 2-aminothiazole concentration and pyridine as an acid acceptor. The analysis was performed using infrared (IR) spectroscopy in Fourier transform IR spectroscopy which is found to be the best method for identification of samples. Conclusions: Among the reaction ratios studied for sulfathiazole, sample with 3:1 ratio of p-acetamidobenzenesulfonyl chloride to 2-aminothiazole with pyridine as an acid acceptor is proved to be the best reactant ratio with yield 91.34%. The process employed for experimentation proved to be an efficient and time-saving process.